(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2016)
Influence of high-dose gamma radiation and particle size on antioxidant properties of maize (Zea mays L.) flour was studied using response surface methodology. A central composite design based on three levels of each of particle size, in terms of mesh number (40, 60 and 80 meshes), and gamma radiation dose (25, 50 and 75 kGy) was constructed. A statistically significant dose-dependent decrease (p